Cost analysis of congenital heart disease patients who underwent diagnostic catheterization - Ni Putu Wirantari; Eka Gunawijaya; Ni Putu Veny Kartika Yantie (Paediatrica Indonesiana, 2020)
Background Cardiac catheterization has developed into an important technique for diagnosis and management of congenital heart disease (CHD) patients. Catheterization is expensive and almost all patients who undergo the procedure at Sanglah General Hospital are participants of the Social Insurance Administration Organization (Badan Penyelenggara Jaminan Sosial/BPJS) that uses the Indonesian Case-Based Groups (INA-CBGs) payment system. Objective To determine the characteristics and analyze costs of CHD patients who underwent diagnostic catheterization. Methods This retrospective study used patient medical record data from March 2009 - July 2018 in Sanglah Hospital, Bali. Data collected included CHD type, age, sex, weight, height, nutritional status, length of procedure, complications, hospital rates, and INA-CBG rates. Data analysis was done with SPSS software. Results Of 219 CHD patients who underwent non-intervention catheterization, most had cyanotic CHD. Catheterization intervention in 2018 showed a discrepancy between the INA-CBG rate and hospital rate. The biggest difference was 107%, in patients who underwent mild heart intervention with class 3 of treatment. Conclusion Most subjects are diagnosed with cyanotic CHD especially tetralogy of Fallot and most has already received intervention. There are negative differences between the INA-CBG rates and the hospital real rates for catheterization.